Does the quality of an embryo differ between long down-regulated and antagonist cycles among age and cycle day 3 FSH-matched women undergoing ART? - (:unkn) unknown (MARMARA UNIV, FAC MEDICINE, 2015)
Objective: Lower pregnancy rates have been reported in gonadotropin releasing hormone (GnRH) antagonist cycles in comparison to those with agonist cycles. A non-significant difference of 3.3% in the pregnancy rate per cycle in favour of GnRH agonists was found. The possible difference between these two protocols could be a limiting factor. We aim to determine if the embryos developed in long down-regulated assisted reproductive technology (ART) cycles differ from the ones obtained in antagonist cycles among women matched for age and follicle-stimulating hormone (FSH) administered on cycle day 3. Patients and Methods: Retrospective cohort analysis was done on a population from a university affiliated hospital. 193 women undergoing standard in vitro fertilization (IVF) or intracytoplasmic sperm injection (ICSI) treatment were included. The age and cycle day 3 FSH matched women undergoing either long or short protocols were compared. Group A consisted of women who had long down-regulation with GnRH analogues, group B consisted of women who had used GnRH antagonists. The clinical and ongoing pregnancy rates were compared. Day 3 embryo scores were compared between the groups. Results: Although mean number of aspirated and inseminated oocytes were similar for the groups and average embryo scores were comparable, clinical and ongoing pregnancy rates were higher in group A than in group B. The percentage of embryos with zero fragmentation and 8-10 blastomeres on day 3 was similar in antagonist and long agonist cycles. Conclusion: Long protocol ART cycles will result in comparable percentages of day 3 embryos with symmetric 8-10 blastomeres with zero fragmentation to those in antagonist cycles.
Keywords: Gonadotropin releasing hormone agonist; Gonadotropin releasing hormone antagonist; Pregnancy; Embryo score; Day 3 embryo; FOLLICLE-STIMULATING-HORMONE; IN-VITRO FERTILIZATION; HUMAN CHORIONIC-GONADOTROPIN; SERUM ESTRADIOL LEVELS; OVARIAN STIMULATION; ASSISTED REPRODUCTION; PREGNANCY RATES; INJECTION; EXPRESSION; LEUPROLIDE